New Exact Solutions for New Model Nonlinear Partial Differential Equation. (18th July 2013) - Maher, A.; El-Hawary, H. M.; Al-Amry, M. S.
Abstract : In this paper we propose a new form of Padé-II equation, namely, a combined Padé-II and modified Padé-II equation. The mapping method is a promising method to solve nonlinear evaluation equations. Therefore, we apply it, to solve the combined Padé-II and modified Padé-II equation. Exact travelling wave solutions are obtained and expressed in terms of hyperbolic functions, trigonometric functions, rational functions, and elliptic functions.